2020
DOI: 10.3390/biology9110407
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Quest for the Structure–Function Relationship of the Mitochondrial Pyruvate Carrier

Abstract: The molecular identity of the mitochondrial pyruvate carrier (MPC) was presented in 2012, forty years after the active transport of cytosolic pyruvate into the mitochondrial matrix was first demonstrated. An impressive amount of in vivo and in vitro studies has since revealed an unexpected interplay between one, two, or even three protein subunits defining different functional MPC assemblies in a metabolic-specific context. These have clear implications in cell homeostasis and disease, and on the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 80 publications
(196 reference statements)
0
8
0
1
Order By: Relevance
“…It is worth noting, however, that Nahgampalli et al reported the functionality of human MPC2 oligomers on their own [ 86 ]. The presence of high order oligomers of MPC2 was observed during cryoelectron microscope examinations of MPC2-EGFP chimeric protein reconstituted in styrene maleic acid lipid particles, although the dominant size of the EGFP tag precluded any conclusion being drawn on the structural organization of the MPC2 oligomer [ 87 ]. Using a yeast homologous expression system, however, Tavoulari et al concluded that MPC homodimers, although they can form, are non-functional [ 81 ].…”
Section: Structure Of Mpcsmentioning
confidence: 99%
“…It is worth noting, however, that Nahgampalli et al reported the functionality of human MPC2 oligomers on their own [ 86 ]. The presence of high order oligomers of MPC2 was observed during cryoelectron microscope examinations of MPC2-EGFP chimeric protein reconstituted in styrene maleic acid lipid particles, although the dominant size of the EGFP tag precluded any conclusion being drawn on the structural organization of the MPC2 oligomer [ 87 ]. Using a yeast homologous expression system, however, Tavoulari et al concluded that MPC homodimers, although they can form, are non-functional [ 81 ].…”
Section: Structure Of Mpcsmentioning
confidence: 99%
“…Because no crystal structures of MPC proteins are available to date, investigation of the structure–function relationship of MPC proteins remains a large challenge . Previous experimental data suggested that yeast MPC1 may have only two transmembrane helices, but MPC2 and MPC3 may contain three transmembrane helices .…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental data suggested that yeast MPC1 may have only two transmembrane helices, but MPC2 and MPC3 may contain three transmembrane helices . As a result, the yeast MPC1/2 and MPC1/3 heterodimers would use five transmembrane helices to form a functional pyruvate transport path in yeast, which seems not feasible because no other transmembrane transporters in the solute carrier (SLC) family (MPC defines a unique SLC family: SLC54A) involve only five transmembrane helices . The smallest carrier in the SLC50 family, that is, the bacterial SemiSWEET glucose transporters, whose functional unit is the homodimer of the SemiSWEET protein, has six transmembrane helices in total. , In addition, other experimental evidence suggests that the yeast MPC1 may possess three transmembrane helices such as MPC2 and MPC3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…José Edwin Neciosup Quesñay, Naomi L. Pollock, Raghavendra Sashi Krishna Nagampalli, Sarah C. Lee, Vijayakumar Balakrishnan, Sandra Martha Gomes Dias, Isabel Moraes, Tim R. Dafforn and Andre Luis Berteli Ambrosio [ 12 ] provide a detailed historical review focused on the human mitochondrial pyruvate transporters (MPC1 and MPC2). Here, they tell the story of the efforts to first identify and subsequently characterise the structure and function of these integral membrane proteins.…”
mentioning
confidence: 99%